modular equivalence for submodule #
Equations
- One or more equations did not get rendered due to their size.
Instances For
theorem
SModEq.def
{R : Type u_1}
[Ring R]
{M : Type u_3}
[AddCommGroup M]
[Module R M]
{U : Submodule R M}
{x : M}
{y : M}
:
x ≡ y [SMOD U] ↔ Submodule.Quotient.mk x = Submodule.Quotient.mk y
theorem
SModEq.map
{R : Type u_1}
[Ring R]
{M : Type u_3}
[AddCommGroup M]
[Module R M]
{U : Submodule R M}
{x : M}
{y : M}
{N : Type u_4}
[AddCommGroup N]
[Module R N]
(hxy : x ≡ y [SMOD U])
(f : M →ₗ[R] N)
:
f x ≡ f y [SMOD Submodule.map f U]
theorem
SModEq.comap
{R : Type u_1}
[Ring R]
{M : Type u_3}
[AddCommGroup M]
[Module R M]
{x : M}
{y : M}
{N : Type u_4}
[AddCommGroup N]
[Module R N]
(V : Submodule R N)
{f : M →ₗ[R] N}
(hxy : f x ≡ f y [SMOD V])
:
x ≡ y [SMOD Submodule.comap f V]
theorem
SModEq.eval
{R : Type u_5}
[CommRing R]
{I : Ideal R}
{x : R}
{y : R}
(h : x ≡ y [SMOD I])
(f : Polynomial R)
:
Polynomial.eval x f ≡ Polynomial.eval y f [SMOD I]